Natural Number Multiplication Distributes over Addition/Proof 3

From ProofWiki
Jump to navigation Jump to search

Theorem

The operation of multiplication is distributive over addition on the set of natural numbers $\N$:

$\forall x, y, z \in \N:$
$\paren {x + y} \times z = \paren {x \times z} + \paren {y \times z}$
$z \times \paren {x + y} = \paren {z \times x} + \paren {z \times y}$


Proof

Using the following axioms:

\((A)\)   $:$     \(\displaystyle \exists_1 1 \in \N_{> 0}:\) \(\displaystyle a \times 1 = a = 1 \times a \)             
\((B)\)   $:$     \(\displaystyle \forall a, b \in \N_{> 0}:\) \(\displaystyle a \times \paren {b + 1} = \paren {a \times b} + a \)             
\((C)\)   $:$     \(\displaystyle \forall a, b \in \N_{> 0}:\) \(\displaystyle a + \paren {b + 1} = \paren {a + b} + 1 \)             
\((D)\)   $:$     \(\displaystyle \forall a \in \N_{> 0}, a \ne 1:\) \(\displaystyle \exists_1 b \in \N_{> 0}: a = b + 1 \)             
\((E)\)   $:$     \(\displaystyle \forall a, b \in \N_{> 0}:\) \(\displaystyle \)Exactly one of these three holds:\( \)             
\(\displaystyle a = b \lor \paren {\exists x \in \N_{> 0}: a + x = b} \lor \paren {\exists y \in \N_{> 0}: a = b + y} \)             
\((F)\)   $:$     \(\displaystyle \forall A \subseteq \N_{> 0}:\) \(\displaystyle \paren {1 \in A \land \paren {z \in A \implies z + 1 \in A} } \implies A = \N_{> 0} \)             


Left Distributive Law for Natural Numbers

First we show that:

$n \times \left({x + y}\right) = \left({n \times x}\right) + \left({n \times y}\right)$


Let us cast the proposition in the form:

$\forall a, b, n \in \N_{> 0}: a \times \paren {b + n} = \paren {a \times b} + \paren {a \times n}$

For all $n \in \N_{> 0}$, let $\map P n$ be the proposition:

$\forall a, b \in \N_{> 0}: a \times \paren {b + n} = \paren {a \times b} + \paren {a \times n}$


Basis for the Induction

$\map P 1$ is the case:

\(\displaystyle a \times \paren {b + 1}\) \(=\) \(\displaystyle \paren {a \times b} + a\) Axiom $B$
\(\displaystyle \) \(=\) \(\displaystyle \paren {a \times b} + \paren {a \times 1}\) Axiom $A$

and so $\map P 1$ holds.


This is our basis for the induction.


Induction Hypothesis

Now we need to show that, if $\map P k$ is true, where $k \ge 1$, then it logically follows that $\map P {k + 1}$ is true.


So this is our induction hypothesis:

$\forall a, b \in \N_{> 0}: a \times \paren {b + k} = \paren {a \times b} + \paren {a \times k}$


Then we need to show:

$\forall a, b \in \N_{> 0}: a \times \paren {b + \paren {k + 1} } = \paren {a \times b} + \paren {a \times \paren {k + 1} }$


Induction Step

This is our induction step:

\(\displaystyle a \times \paren {b + \paren {k + 1} }\) \(=\) \(\displaystyle a \times \paren {\paren {b + k} + 1}\) Axiom $C$
\(\displaystyle \) \(=\) \(\displaystyle \paren {a \times \paren {b + k} } + a\) Axiom $B$
\(\displaystyle \) \(=\) \(\displaystyle \paren {\paren {a \times b} + \paren {a \times k} } + a\) Induction hypothesis
\(\displaystyle \) \(=\) \(\displaystyle \paren {a \times b} + \paren {\paren {a \times k} + a}\) Natural Number Addition is Associative
\(\displaystyle \) \(=\) \(\displaystyle \paren {a \times b} + \paren {a \times \paren {k + 1} }\) Axiom $B$

The result follows by the Principle of Mathematical Induction.

$\Box$


Right Distributive Law for Natural Numbers

Then we show that:

$\left({x + y}\right) \times n = \left({x \times n}\right) + \left({y \times n}\right)$


For all $n \in \N_{> 0}$, let $\map P n$ be the proposition:

$\forall a, b \in \N_{> 0}: \paren {a + b} \times n = \paren {a \times n} + \paren {b \times n}$


Basis for the Induction

$\map P 1$ is the case:

\(\displaystyle \paren {a + b} \times 1\) \(=\) \(\displaystyle a + b\) Axiom $A$
\(\displaystyle \) \(=\) \(\displaystyle \paren {a \times 1} + \paren {b \times 1}\) Axiom $A$

and so $\map P 1$ holds.


This is our basis for the induction.


Induction Hypothesis

Now we need to show that, if $\map P k$ is true, where $k \ge 0$, then it logically follows that $\map P {k + 1}$ is true.


So this is our induction hypothesis:

$\forall a, b \in \N_{> 0}: \paren {a + b} \times k = \paren {a \times k} + \paren {b \times k}$


Then we need to show:

$\forall a, b \in \N_{> 0}: \paren {a + b} \times \paren {k + 1} = \paren {a \times \paren {k + 1} } + \paren {b \times \paren {k + 1} }$


Induction Step

This is our induction step:

\(\displaystyle \paren {a + b} \times \paren {k + 1}\) \(=\) \(\displaystyle \paren {\paren {a + b} \times k} + \paren {a + b}\) Axiom $B$
\(\displaystyle \) \(=\) \(\displaystyle \paren {\paren {a \times k} + \paren {b \times k} } + \paren {a + b}\) Induction hypothesis
\(\displaystyle \) \(=\) \(\displaystyle \paren {\paren {a \times k} + a} + \paren {\paren {b \times k} + b}\) Natural Number Addition is Commutative
\(\displaystyle \) \(=\) \(\displaystyle \paren {a \times \paren {k + 1} } + \paren {b \times \paren {k + 1} }\) Axiom $B$

The result follows by the Principle of Mathematical Induction.

$\Box$

The result follows.

$\blacksquare$


Sources